The development of a typology of identity, unhealthy, and dangerous jobs in Costa Rica - Chavés Rodríguez, Jouseth (2025)
The Costa Rican Labor Code contains labor subcategories classified as heavy, unhealthy, and dangerous, whose nature is based on protecting the health of the workers who perform them. Despite the importance of this legal determination for workers, there are great difficulties in identifying whether or not heavy work is being performed. This creates a high degree of legal and physical insecurity for workers, who are forced to put their physical integrity, health, and lives at risk. This study seeks to contribute to the development of a typology of heavy, unhealthy, and dangerous work for practical application, with the aim of identifying, defining, and applying regulations to this type of work.